2017
DOI: 10.1063/1.4975014
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of spin current contribution to spectrum of electromagnetic waves in spin-1/2 plasma. I. Dielectric permeability tensor for magnetized plasmas

Abstract: The dielectric permeability tensor for spin polarized plasmas is derived in terms of the spin-1/2 quantum kinetic model in six-dimensional phase space. Expressions for the distribution function and spin distribution function are derived in linear approximations on the path of dielectric permeability tensor derivation. The dielectric permeability tensor is derived the spin-polarized degenerate electron gas. It is also discussed at the finite temperature regime, where the equilibrium distribution function is pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…The kinetic model of degenerate electron gas presented in Refs. [16], [17] does not show influence of the spin dynamics on the Bernstein mode spectrum. Moreover, there is an extra spin caused transverse wave which is called the zeroth cyclotron wave [4], [17].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The kinetic model of degenerate electron gas presented in Refs. [16], [17] does not show influence of the spin dynamics on the Bernstein mode spectrum. Moreover, there is an extra spin caused transverse wave which is called the zeroth cyclotron wave [4], [17].…”
Section: Introductionmentioning
confidence: 82%
“…There is a paper on the kinetic model with the SSE [15]. These papers [16,17] deal with the single fluid kinetic model of electrons, but different distributions for electrons with different spin projections are introduced at the derivation of the equilibrium distribution functions.…”
Section: Introductionmentioning
confidence: 99%
“…The electron spin effect is another quantum effect that has been extensively studied in the plasma waves and instabilities during the last decade. [30][31][32][33][34] Contrib. [19,20] Moreover, to understand the non-linear dynamics of spin-1/2 quantum plasmas, the QHD model for spin-1/2 particles has been derived and its usefulness demonstrated in solid-state plasma as well as in astrophysical plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Subsequently, the kinetic quantum model for spin-1/2 quantum plasmas was developed and was applied to study the dispersion properties of different plasma waves. [30][31][32][33][34] Contrib. Plasma Phys.…”
mentioning
confidence: 99%
“…Corresponding research is performed in Refs. [6,7]. It is shown that the kinetic analysis can be done with non-zero equilibrium scalar distribution function f 0 and non-zero z-projection of the equilibrium spin distribution function S 0z while S 0x = S 0y = 0 [6,7].…”
Section: Introductionmentioning
confidence: 99%